2023
DOI: 10.1002/fsn3.3433
|View full text |Cite
|
Sign up to set email alerts
|

Cookies enriched with anethole and secoisolariciresinol diglucoside from flaxseed and fennel seeds improve hypercholesterolemia, lipid profile, and liver functions: A pilot study

Abstract: Over millennia, flaxseeds and fennel seeds have captured greater attention owing to the broad spectrum of bioactive compounds and their respective therapeutic potential. They are well-known therapeutic plants, frequently used in home treatments for a variety of medical conditions. The novelty of this pilot study is to assess the beneficial health effects of secoisolariciresinol diglucoside (SDG) and anethole-based enriched cookies among hyperlipidemic patients. The result of sensory evaluation revealed that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Baked products are the most common foods containing flaxseed. Baking at temperatures as high as 178°C for 2 h, for example, had no effect on the composition or concentration of ALA in a cooked muffin (Chen et al, 1994 ; Noreen, Rehman, et al, 2023 ; Noreen, Tufail, Badar Ul Ain, Awuchi, 2023 ; Noreen, Tufail, Badar Ul Ain, Ali, et al, 2023 ; Noreen, Tufail, Tufail, et al, 2023 ). The addition of flavoring to baked goods also allows for the masking of any less‐than‐ideal flavor character caused by flaxseed bitterness or slight rancidity.…”
Section: Uses and Important Applications Of Flaxseedmentioning
confidence: 99%
See 3 more Smart Citations
“…Baked products are the most common foods containing flaxseed. Baking at temperatures as high as 178°C for 2 h, for example, had no effect on the composition or concentration of ALA in a cooked muffin (Chen et al, 1994 ; Noreen, Rehman, et al, 2023 ; Noreen, Tufail, Badar Ul Ain, Awuchi, 2023 ; Noreen, Tufail, Badar Ul Ain, Ali, et al, 2023 ; Noreen, Tufail, Tufail, et al, 2023 ). The addition of flavoring to baked goods also allows for the masking of any less‐than‐ideal flavor character caused by flaxseed bitterness or slight rancidity.…”
Section: Uses and Important Applications Of Flaxseedmentioning
confidence: 99%
“…The results revealed that flaxseed supplementation was tolerated well by the patients and led to exceptional and consistent decreased levels of LDL and total cholesterol. However, it had no significant effects on lipoprotein a, interleukin 6 (IL‐6), and C‐reactive protein (CRP) (Kanikowska et al, 2020 ; Noreen, Rehman, et al, 2023 ; Noreen, Tufail, Badar Ul Ain, Awuchi, 2023 ; Noreen, Tufail, Badar Ul Ain, Ali, et al, 2023 ; Noreen, Tufail, Tufail, et al, 2023 ). A report suggested that 15 g of ground flaxseed consumed by hyperlipidemic patients on long‐term consumption of Vitamin E (800 IU per day) significantly reduced serum cholesterol in elderly subjects enrolled in a 3‐month feeding trial.…”
Section: Flaxseed and Hyperlipidemiamentioning
confidence: 99%
See 2 more Smart Citations